2019
DOI: 10.1038/s41366-019-0340-1
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor agonist indigo protects against obesity-related insulin resistance through modulation of intestinal and metabolic tissue immunity

Abstract: Background/objectives Low-grade chronic inflammation in visceral adipose tissue and the intestines are important drivers of obesity associated insulin resistance. Bioactive compounds derived from plants are an important source of potential novel therapies for the treatment of chronic diseases. In search for new immune based treatments of obesity associated insulin resistance, we screened for tissue relevant anti-inflammatory properties in 20 plant-based extracts. Methods We screened 20 plant-based extracts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 77 publications
1
43
0
Order By: Relevance
“…aeruginosa pigment molecule, pyocyanin, also an AHR activator, caused inhibition of adipogenesis resulting in wasting syndrome [ 73 ]. A recent study identified indigo, a naturally occurring AHR ligand, as having anti-inflammatory properties in visceral adipose tissue that effectively protected against HFD-induced glucose intolerance [ 74 ]. In another study it was shown that people and animals with metabolic syndrome had reduced levels of AHR agonist activity in fecal samples [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa pigment molecule, pyocyanin, also an AHR activator, caused inhibition of adipogenesis resulting in wasting syndrome [ 73 ]. A recent study identified indigo, a naturally occurring AHR ligand, as having anti-inflammatory properties in visceral adipose tissue that effectively protected against HFD-induced glucose intolerance [ 74 ]. In another study it was shown that people and animals with metabolic syndrome had reduced levels of AHR agonist activity in fecal samples [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because maintenance of intestinal homeostasis is increasingly recognized as an important therapeutic target in obesity and NASH, we then investigated whether Mt-P was beneficial in a rodent model of diet-induced NASH. NASH is a highly prevalent human disorder associated with metabolic syndrome and sub-clinical inflammation, for which therapy remains suboptimal [14,46,47,48,49]. Results shown in Figure 8, Figure 9 and Figure 10 and supplementary Figures S4–S6 demonstrate that treating mice with Mt-P at the dose of 5 mg/kg/day effectively protected from body weight gain, development of insulin resistance, and metabolic dysfunction caused by HFD-F.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, supplementation of diet with AhR agonists or a Lactobacillus strain naturally producing AhR ligands improved metabolic impairments [ 67 ]. Furthermore, the AhR agonist indigo has been described to protect against obesity-related insulin resistance through modulation of intestinal and metabolic tissue immunity [ 69 ]. Lin et al, suggest that the AhR ligand indigo has therapeutic potential to modulate inflammatory signals in obesity.…”
Section: Tryptophan Metabolism Pathways and Ahr In Diseasementioning
confidence: 99%
“…Lin et al, suggest that the AhR ligand indigo has therapeutic potential to modulate inflammatory signals in obesity. Moreover, AhR activation is known to decrease serum glucose and triglyceride concentrations, described highly increased in patients suffering from obesity and metabolic syndrome [ 69 ]. AhR deficiency has been linked with dyslipidemia and dysbalanced glucose homeostasis, two parameters known to contribute to the development of type 2 diabetes in humans [ 70 ].…”
Section: Tryptophan Metabolism Pathways and Ahr In Diseasementioning
confidence: 99%